2011
DOI: 10.3354/meps08869
|View full text |Cite
|
Sign up to set email alerts
|

Macroalgae reduce growth of juvenile corals but protect them from parrotfish damage

Abstract: Inhibition of early life stages of corals by benthic algae is a critical bottleneck to the recovery and resilience of corals. Increasingly frequent and severe disturbances are causing largescale coral mortality, usually followed by colonisation and dominance by benthic algae. The capacity of corals to re-establish in such algal-dominated habitats will depend on the effects of the algae on growth and survivorship of juvenile corals. We experimentally evaluated the competition between juvenile corals Porites ast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
49
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(53 citation statements)
references
References 39 publications
2
49
0
2
Order By: Relevance
“…Given that incidence of predation were not quantified in this study, these conclusions remain speculative, but studies in old non-Caribbean reserves have reported that corallivory causes retarded recovery after disturbances . Nonetheless, the patterns observed here and the findings of a recent study (Venera-Ponton et al 2011) suggest that coralalgal inter actions are considerably more complicated and that additional factors are involved than proposed by the common coral-algal competition hypo theses.…”
Section: Experimental Treatment Effectssupporting
confidence: 47%
See 4 more Smart Citations
“…Given that incidence of predation were not quantified in this study, these conclusions remain speculative, but studies in old non-Caribbean reserves have reported that corallivory causes retarded recovery after disturbances . Nonetheless, the patterns observed here and the findings of a recent study (Venera-Ponton et al 2011) suggest that coralalgal inter actions are considerably more complicated and that additional factors are involved than proposed by the common coral-algal competition hypo theses.…”
Section: Experimental Treatment Effectssupporting
confidence: 47%
“…Consequently, other factors such as recruitment limits, temperature anomalies, disease, and predation pressure could be more important than macro algae in determining these species' health and survival (Vu et al 2009, Venera-Ponton et al 2011). Many of the small-scale experimental manipulations show immediate responses on the order of days to weeks (Smith et al 2006, Liu et al 2009), which we suggest are largely a result of experimental conditions that are atypical of field conditions.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations